Philippines Cash Cropping Project, Southern Bukidnon Province, 1984-1985 - International Food Policy Research Institute (International Food Policy Research Institute, 2000)
The questionnaire was administered in 4 rounds over two years to approximately 450 households. Topics include household information; parcels of land owned and cultivated; production of sugar, corn, rice, and other crops; agricultural wage labor; other sources of income; backyard production; assets; food and non-food expenditures; preschool feeding; health services and nutritional knowledge; time allocation; anthropometry and morbidity; and household food intake.